2009
DOI: 10.1177/1553350609339375
|View full text |Cite
|
Sign up to set email alerts
|

New Hybrid Approach for NOTES Transvaginal Cholecystectomy: Preliminary Clinical Experience

Abstract: Transvaginal NOTES is a feasible and safe alternative for cholecystectomy in this preliminary clinical experience, allowing good cosmetic benefits and low analgesic requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…Results of the observational study presented here show no difference in operative time among the evaluated procedures and are in accordance with other published data [4,9,12,15,16]. Some authors even reported significantly longer operative times with the new procedures [2,7,10,11,14,17]. Shorter times have been reported, especially for transvaginal cholecystectomy [13,18].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Results of the observational study presented here show no difference in operative time among the evaluated procedures and are in accordance with other published data [4,9,12,15,16]. Some authors even reported significantly longer operative times with the new procedures [2,7,10,11,14,17]. Shorter times have been reported, especially for transvaginal cholecystectomy [13,18].…”
Section: Discussionsupporting
confidence: 93%
“…The first prospective randomised study of single-port cholecystectomy in 40 patients was published this year, but it was only double armed [17]. Most of the published data are feasibility studies, retrospective data analyses, 'how we do it' manuscripts or limited two-armed prospective data collections [1,3,4,7,9,10,[12][13][14][15][16][18][19][20]. Up to now, no prospective three-armed study comparing 'conventional' laparoscopic, single-incision and transvaginal cholecystectomy has been published.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Marescaux [3]. Since then, transvaginal access has become the preferred route for NOTES procedures with the international experience now numbering several hundred cases performed, including cholecystectomy, nephrectomy, sleeve gastrectomy, and segmental colon resection [4][5][6][7][8][9]. The major limitation of the approach is that it can only be performed in women.…”
mentioning
confidence: 99%
“…Publicações recentes e apresentações em eventos científicos desde 2007 descreveram as aplicações clínicas iniciais do novo método, após aprovação [14][15][16][17] , outros grupos seguiram e publicaram seus resultados clínicos iniciais das técnicas, na maior parte com assistencia laparoscópica para propósito de retração ou visualização [18][19][20][21][22][23][24][25][26][27][28] . Apendicectomia transgástrica foi também apresentada clinicamente em congressos por Rao e Reddy utilizando material endoscópico disponível desde 2005 29 , e recuperação bem-sucedida de gastrostomia foi descrita por Marks e cols 30 .…”
Section: Discussionunclassified